2017
DOI: 10.4103/0973-1075.197945
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of pilates and mckenzie training on pain and general health in men with chronic low back pain: A randomized trial

Abstract: Background:Today, chronic low back pain is one of the special challenges in healthcare. There is no unique approach to treat chronic low back pain. A variety of methods are used for the treatment of low back pain, but the effects of these methods have not yet been investigated adequately.Aim:The aim of this study was to compare the effects of Pilates and McKenzie training on pain and general health of men with chronic low back pain.Materials and Methods:Thirty-six patients with chronic low back pain were chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…We conclude that all the analyzed techniques have proved their efficacy with respect to the CG, but it is difficult to affirm the superiority of one approach as compared to another; they are more or less equivalent in reducing pain, reducing disability and improving the QoL. Some of the studies reported in this review included CG of patients who did not perform any rehabilitative treatment;16,19,31,33,40,47 other studies used the patient’s delivery of an information booklet about home-based exercises or ergonomic advices. These research studies concluded about a non-resolution of CLBP in the untreated group, that the natural history of progression of untreated lumbar chronic pain is to remain so with peaks of recurrences and a floating but unresolved pain.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…We conclude that all the analyzed techniques have proved their efficacy with respect to the CG, but it is difficult to affirm the superiority of one approach as compared to another; they are more or less equivalent in reducing pain, reducing disability and improving the QoL. Some of the studies reported in this review included CG of patients who did not perform any rehabilitative treatment;16,19,31,33,40,47 other studies used the patient’s delivery of an information booklet about home-based exercises or ergonomic advices. These research studies concluded about a non-resolution of CLBP in the untreated group, that the natural history of progression of untreated lumbar chronic pain is to remain so with peaks of recurrences and a floating but unresolved pain.…”
Section: Resultsmentioning
confidence: 87%
“…In the MK group, participants performed 1-hour of workouts for 20 days while the pilates group practiced sessions 3 times a week for 6 weeks and both were compared with CGs. After therapeutic exercises, no big difference in pain relief was found between the pilates group and the MK group ( P =0.327) but an improvement in pain score was seen in both techniques when compared to the CG 16…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, three trials have been released, comparing the effectiveness of Pilates to another methods widely used in the management of CNLBP 32 33…”
Section: The Standardisation Of Pilates Training In Cnlbpmentioning
confidence: 99%
“…This can be seen in the strong improvement of patients in this group over the time course of the study, although, strictly speaking, a no-treatment control would have to be documented in order to definitively prove this. But we can assume that most chronic patients would not improve to the same degree naturally during 5 or 6 weeks [47]. Against this background, it is interesting to see that, in addition to the significant time trend, all analyses show a stronger improvement with PPT that is significantly different from physiotherapy.…”
Section: Discussionmentioning
confidence: 88%